2018
DOI: 10.1002/pat.4316
|View full text |Cite
|
Sign up to set email alerts
|

Development of completely bio‐based epoxy networks derived from epoxidized linseed and castor oil cured with citric acid

Abstract: Bio‐based epoxy resins were synthesized from nonedible resources like linseed oil and castor oil. Both the oils were epoxidized through in situ method and characterized via Fourier transform infrared and 1H‐NMR. These epoxidized oils were crosslinked with citric acid without using any catalyst and their properties compared with diglycidyl ether of bisphenol A‐epoxy. The tensile strength and modulus of epoxidized linseed oil (ELO) were found to be more than those of epoxidized castor oil (ECO)‐based network. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 37 publications
2
41
0
2
Order By: Relevance
“…A comparison with the work of Sahoo et al show that the use of citric acid, which is a triacid, as hardener results in a 10 times higher cross‐link density. [ 25 ] From Table 2, it can be concluded that the T α and the crosslink density of ELO/suberic and ELO/sebacic systems are very similar. The T α is much lower for these two systems in comparison with ELO/succinic system, while the differences in crosslink density are weak.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A comparison with the work of Sahoo et al show that the use of citric acid, which is a triacid, as hardener results in a 10 times higher cross‐link density. [ 25 ] From Table 2, it can be concluded that the T α and the crosslink density of ELO/suberic and ELO/sebacic systems are very similar. The T α is much lower for these two systems in comparison with ELO/succinic system, while the differences in crosslink density are weak.…”
Section: Resultsmentioning
confidence: 98%
“…This degradation phenomenon can be attributed to ester and ether chain scissions formed thanks to the reaction between dicarboxylic acids and ELO. [ 25 ] The last degradation step at around 530°C corresponds to the carbonization. These steps occur in the same T range as reported by Ding et al [ 17 ] and Falco et al [ 49 ] for ELO cured with aliphatic diacids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, epoxidation is the most preferred process for hydroxyl functionalization of plant-based oils. [55][56][57] Since the conversion of double bonds into epoxide ring is done using various methods such as i) in situ epoxidation using peracids such as peracetic acid or perbenzoic acid in the presence of an acid catalyst, ii) epoxidation of double bond with organic and inorganic peroxides, including transition metal catalysts, iii) epoxidation with halohydrins using hypohalous acids and their salts, and iv) epoxidation with molecular oxygen. Figure 5 depicts the reaction of epoxidation using acetic acid and hydrogen peroxide in the presence of an acid catalyst.…”
Section: Epoxidation and Epoxide Ring-openingmentioning
confidence: 99%
“…In an environmental context, concerns about the reduction of the carbon footprint is growing rapidly with the development of bio‐based polymers. Many epoxy networks based on renewable resources have been developed recently from epoxidized natural oils, such as soybean oil, linseed oil, and castor oil . However, all of these triglycerides exhibit similar structures with long flexible chains which provide low thermal or mechanical properties induced by a low crosslinking density and T g .…”
Section: Introductionmentioning
confidence: 99%